2002
DOI: 10.1038/sj.onc.1205878
|View full text |Cite
|
Sign up to set email alerts
|

Selective silencing of viral gene expression in HPV-positive human cervical carcinoma cells treated with siRNA, a primer of RNA interference

Abstract: Selective silencing of mammalian gene expression has recently been achieved using short interfering RNA (siRNA). Synthetic siRNA targets homologous mRNA for degradation and the process is highly efficient. Here we demonstrate siRNA silencing of pathogenic viral gene expression. As a well characterized model we chose cervical carcinoma cells positive for human papillomavirus type 16. Over 90% of human cervical cancers are positive for papillomavirus and abnormal cell proliferation is driven by co-operative effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
273
5
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 342 publications
(300 citation statements)
references
References 30 publications
21
273
5
1
Order By: Relevance
“…In this study, we have demonstrated that an siRNA of hWAPL induces tumour regression in vivo. This anticancer effects by the hWAPL siRNA stands comparison with the effects of the E6 siRNA (Jiang and Milner, 2002;Butz et al, 2003;Yoshinouchi et al, 2003). Therefore, we expect that hWAPL is one of strong candidates as a target for uterine cervical cancer therapy.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…In this study, we have demonstrated that an siRNA of hWAPL induces tumour regression in vivo. This anticancer effects by the hWAPL siRNA stands comparison with the effects of the E6 siRNA (Jiang and Milner, 2002;Butz et al, 2003;Yoshinouchi et al, 2003). Therefore, we expect that hWAPL is one of strong candidates as a target for uterine cervical cancer therapy.…”
Section: Discussionmentioning
confidence: 85%
“…For uterine cervical cancer, HPV E6 and/or E7 were shown to be a strong candidate as a target for gene-specific therapy (Jiang and Milner, 2002;Butz et al, 2003;Yoshinouchi et al, 2003). However, many subtypes of high-risk HPV have been detected in cervical cancers although HPV types 16 and 18 are great majority of cervical carcinomas (Nakagawa et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…siRNA-mediated silencing of HPV16 E6 reduces endogenous CAL levels in Caski cells It has been reported that siRNA-mediated depletion of E6 or E6AP mRNA causes stabilization and nuclear accumulation of p53 (Jiang and Milner, 2002;Yoshinouchi et al, 2003). To show that CAL can be destabilized by E6 or E6AP under physiological conditions, we examined whether siRNAs against HPV16 E6 (siE6) or against E6AP (siE6AP) affected CAL in Caski cells, an HPV-positive cell line.…”
Section: Hpv16 E6 Enhances the Degradation Of Calmentioning
confidence: 99%